Graphene‐Driven Metadevice for Active Microwave Camouflage with High‐Efficiency Transmission Window. Issue 2 (13th December 2020) - Huang, Cheng; Yang, Jianing; Ji, Chen; Yuan, Liming; Luo, Xiangang
Abstract: The general method to achieve electromagnetic (EM) invisibility is to use absorbing materials that can reduce the backscattering microwave signals. However, they will influence the transmission of useful signals, and their passive operation mode also blocks the realization of active camouflage systems. Here, the authors propose an electrically tunable metadevice which can dynamically manipulate the reflection magnitude and realize high‐efficiency transmission at two distinctive frequency bands. Such a metadevice is driven by graphene sandwich structure integrated with multi‐layer metasurface. By electrically controlling the sheet resistance of graphene, the authors have experimentally verified that the metadevice can tune the reflection magnitude from −5 to −20 dB over a wide frequency band of 5–15 GHz, and meanwhile realize a high transparent EM window with 3‐dB transmission band covering from 23 to 25 GHz. The operation mechanism is discussed by examining the electric field distribution and also employing an equivalent circuit model to analyze the input impedance. Furthermore, using the developed metadevice, the authors still demonstrate its dynamical camouflaging performance and application potential as an antenna radome by experiment. The finding in this study is expected to trigger great interest in adaptive camouflage, stealth radome, and multifunctional EM manipulation fields. Abstract : An electrically tunable metadevice driven by graphene is presented, which can achieve dynamical manipulation of the reflected wave magnitude and meanwhile generate an electromagnetic transparent window at two distinctive frequency bands. Using the above two functionalities, this metadevice can be not only developed for wideband adaptive camouflage, but also treated as an antenna radome for signal transmission.